Identification and operationalisation of indicators to monitor successful uptake of advance care planning policies: a modified Delphi study. Issue Volume 12:Issue e3(2022) (12th February 2021) - Fassbender, Konrad; Biondo, Patricia; Holroyd-Leduc, Jayna; Potapov, Alexei; Wityk Martin, Tracy Lynn; Wasylenko, Eric; Hagen, Neil Angus; Simon, Jessica
Abstract : Background: In 2014, the province of Alberta, Canada implemented a province-wide policy and procedures for advance care planning (ACP) and goals of care designation (GCD) across its complex, integrated public healthcare system. This study was conducted to identify and operationalise performance indicators for ACP/GCD to monitor policy implementation success and sustainment of ACP/GCD practice change. Methods: A systematic review and environmental scan was conducted to identify potential indicators of ACP/GCD uptake (n=132). A purposive sample of ACP/GCD stakeholders was invited to participate in a modified Delphi study to evaluate, reduce and refine these indicators through a combination of face-to-face meetings and online surveys. Results: An evidence-informed Donabedian by Institute of Medicine (IOM) framework was adopted as an organising matrix for the indicators in an initial face-to-face meeting. Three online survey rounds reduced and refined the 132 indicators to 18. A final face-to-face meeting operationalised the indicators into a measurable format. Nine indicators, covering 11 of the 18 Donabedian×IOM domains, were operationalised. Conclusions: Nine ACP/GCD evidence-informed indicators mapping to 11 of 18 Donabedian×IOM domains were endorsed, and have been operationalised into an online ACP/GCD dashboard. The indicators provide a characterisation of ACP/GCD uptake that could be generalised to other healthcare settings, measuring aspects related to ACP/GCD documentation, patient satisfaction and agreement between medical orders and care received. The final nine indicators reflect the stakeholders' expressed intent to strike a balance between comprehensiveness and feasibility within a large provincial healthcare system.